Aging and the family : understanding changes in structural and relationship dynamics - Claster, Patricia Neff; Blair, Sampson Lee (Contemporary perspectives on family research, 2021)
As family structures continue to evolve, aging relatives have caused increasing concern for family members as they attempt to manage complex issues such as health, caregiving, emotional and instrumental support, and intergenerational relationships. This multidisciplinary volume focuses on how aging interacts with family structures and relationship dynamics. Including research from around the globe, the authors address a wide array of topics, including family support networks, elderly care, grandparenthood, marital dynamics and satisfaction, elderly divorce, cohabitation, gender, and intergenerational relationships, and more. Paying homage to the fact that the manners by which aging affects families can vary considerably from one culture to another, this collection makes a crucial contribution by collating research on aging and the family from an international perspective. Providing this wide scope of quality research, the volume equips readers to better assess how aging and its related issues are affecting families from multiple backgrounds.